Penilaian Kinerja Berbasis Balanced Scorecards (BSC) untuk Melakukan Rancang Ulang Strategi Bersaing - Sumban, Asdiana Dua; Zuhroh, Diana; Parawiyati, Parawiyati (University of Merdeka Malang, 2021)
The objectives of this study are to evaluate the performance of the Kusuma Agrowisata Hotel during the Covid-19 pandemic and to design the business strategy for the Hotel in new normal period. This research applies the quantitative and qualitative method. The data were obtained using questionnaires and interview and analyzed by applying descriptive statistics, using the Balanced Scorecard and SWOT analysis. The result shows that the hotel was less successful in improving revenue and efficiency. However the customers were satisfied and the hotel was able to achieve the company's strategy efficiency index and the staff satisfaction index. The SWOT analysis found out that there was S-O Strategy which could be done by keeping the room prices competitive, providing children’s playground, keeping the good image, having a strategic location, maintaining the friendliness, maintaining the surrounding natural environment, keeping the guest demand fulfilled, reopening various tourist sites and setting strategies to eliminate customers boredom.